ESTUDO DA DEGRADAÇÃO DE NANOCOMPÓSITOS DE POLIPROPILENO COM ARGILA MONTMORILONITA APÓS MÚLTIPLOS REPROCESSOS - Silvano, Josiane da Rocha (2012)
The nanocomposites of polypropylene (PP) and montmorillonite (MMT) were prepared using a twin screw extruder and reprocessed five times. Whereas the nonpolar nature of the PP was used two different types of coupling agent grafted the polypropylene with maleic anhydride (PP-g-MA) and polypropylene grafted with Acrylic Acid (AA-g-PP) in order to improve the merge process. Samples containing 1,3 and 5% clay obtained at the 3:1 mass ratio of compatibilizer / clay and evaluated the effect of degradation was quantified by X-ray diffraction, infrared spectroscopy,rheological behavior. Formation of color through the system CIE lab and crystallization kinetics. The results of FTIR and Colorimentry followed the same trend with formation of carbonyl number of reworks and rheological analysis show a reduction on molecular weight due to the process of thermo-mechanical degradation of PP and also showed that for the sample containing 5% clay PP-g-MA as a compatibilizer network percolated presented showing that a good dispersion to formulation. Regarding the process of crystallization was observed that the incorporation of MMT promoted a nucleating effect on the PP. The influence of the compatibilizing agent was observed that the PP-g-AA had a nucleating effect additional to the PP / MMT. Regarding the compatibilizer PP-g-MA was observed that the nucleating effect does not occur on the PP Pure occurring including the inhibition of the nucleating effect on the PP/MMT. The influence of the number of extrusions on the crystallisation process, there is generally a strong effect of accelerating the crystallization kinetics due to the increased number of reprocessing.